Growing Bell Peppers in Soilless Culture under Open Shade Structures - Robert C. Hochmuth; Danielle D. Treadwell; Eric H. Simonne; Linda B. Landrum; Wanda L. Laughlin; Lei Lani Davis (EDIS)
HS-1113, a 4-page illustrated fact sheet by Robert C. Hochmuth, Danielle D. Treadwell, Eric H. Simonne, Linda B. Landrum, Wanda L. Laughlin, and Lei Lani Davis, describes the results of trials of using soilless culture and shade to extend the bell pepper growing season through the hottest part of the summer and into fall. Includes tables of trial data. Published by the UF Department of Horticultural Sciences, July 2007.